The situation of peasants in agriculture of Khiva khanate in the XIX century - Bakirova Dinora Kholmurod qizi; Bozorov Muhammad Alijon o’g’li; Bakirova Mohigul Kholmurod qizi (Research Parks Publishing LLC, 2020)
The article provides information about the main productive forces in the agriculture of the Khiva khanate in the XIX century: the living conditions of tenants, peasants and slaves, as well as their tax obligations.